Recent progress in the treatment of uveitic macular edema. (3rd September 2019) - Adán, Alfredo; Moll-Udina, Aina; Alba-Linero, Carmen; Figueroa-Vercellino, Juan Pablo; Llorenç, Victor
ABSTRACT: Introduction : Macular edema (ME) is defined as a thickening of the macular area, which results from a breakdown of the outer and/or inner blood-retina barrier. It is usually accompanied by quantity and quality loss of central vision. Uveitic macular edema (UME) is a leading cause of visual loss due to macular edema chronification. A number of treatment options are available for UME including periocular and intravitreal corticosteroids, immunosuppressants and biological agents. Pars plana vitrectomy also plays a role in refractory patients. Areas covered : We herein provide a summary of current options to treat UME, highlighting strengths and weaknesses on the basis of available literature and self-experience. Expert opinion : Visual prognosis in uveitis has improved as treatment of macular edema has done in the last decade. Corticosteroid slow-release intravitreal implants as well as anti-TNF and anti-IL-6 biologic drugs have been the cornerstone of these medical advances.